2022
DOI: 10.1111/jce.15343
|View full text |Cite
|
Sign up to set email alerts
|

Leadless pacemaker perforations: Clinical consequences and related device and user problems

Abstract: Background Cardiac perforation during leadless pacemaker implantation is more likely to require intervention than perforation by a transvenous lead. This study reports the consequences of Micra pacemaker perforations and related device and operator use problems based on information the manufacturer has submitted to the Food and Drug Administration (FDA). Methods FDA's Manufacturer and User Facility Device Experience (MAUDE) database was searched for Micra perforations. Data extracted included deaths, major adv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Being an observational study, it may be conceptualized that HS implantation of LP was sought by the operating physician to avoid complications compared to the AS position. A prior study by Hauser et al 16 . showed that HS LP implantation was associated with a lower risk of perforation.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Being an observational study, it may be conceptualized that HS implantation of LP was sought by the operating physician to avoid complications compared to the AS position. A prior study by Hauser et al 16 . showed that HS LP implantation was associated with a lower risk of perforation.…”
Section: Discussionmentioning
confidence: 93%
“…Being an observational study, it may be conceptualized that HS implantation of LP was sought by the operating physician to avoid complications compared to the AS position. A prior study by Hauser et al 16 showed that HS LP implantation was associated with a lower risk of perforation. However, this hypothesis seems less plausible based on our study results, because: (1) in our study, the number of deployment attempts that was needed to get the LP in an optimal location (a potential surrogate for procedural and anatomical complexity) and complication rates were similar in the AS group compared to the HS group (Tables 1), and (2) if avoiding complications was really the intent, then it is possible that the HS LP group was likely a sicker/fail group of patients compared to the AS group.…”
Section: Hs Pacing Versus As Pacingmentioning
confidence: 93%
“…Data from a real-world setting showed that 36% (82/228) of pericardial effusion patients had the need for pericardiocentesis, and 11.5% (26/228) required a thoracotomy. A higher proportion (26% (146/563)) of Micra-related perforations requiring emergency surgery was also reported in the MAUDE [ 37 ].…”
Section: Leadless Ventricular Pacemakersmentioning
confidence: 86%
“…24 While transcatheter leadless pacemakers are another consideration for pacing, there have been reports of tricuspid valve injury during implantation necessitating surgical intervention. 27 Additionally, recent literature reported complications in 10 of 62 pediatric patients who underwent transvenous leadless pacemaker implantation, including cardiac perforation and femoral venous thrombus. 28 Therefore, CNA may be an alternative treatment for pediatric patients with severe functional pauses, particularly those with a lower weight, with the potential for less morbidity than pacemaker implantation.…”
Section: Discussionmentioning
confidence: 99%